Liparis condylobulbon Reichb. f. from Gumitir, Indonesia: Morphology, Molecular, and Phytochemical Profile - Ulum, Fuad Bahrul; Arum, Asyifa Yasmin; Sa’adah, Kurnia; Setyati, Dwi; Dwinianti, Edia Fitria; Rajamani, Ranjithkumar; Nugraha, Ari Satia; Su’udi, Mukhamad (UI Scholars Hub, 2026)
Liparis condylobulbon Rchb.f. is an epiphytic orchid across South and Southeast Asia, which holds notable ethnomedicinal and pharmacological significance. This study aims to characterize Indonesian Liparis condylobulbon using integrated morphological, molecular (matK, rbcL, ITS2), and phytochemical (LC-MS, DPPH) analyses of specimens from Mount Gumitir, providing the first comprehensive taxonomic and pharmacological profile to support species authentication and future bioprospecting. The L. condylobulbon specimen displays diagnostic epiphytic morpho-logy, including fusiform pseudobulbs, two elongate leaves, and an erect inflorescence bearing 123 flowers. Molecular barcoding using matK, rbcL, and ITS2 confirmed its identity, with phylogenetic analyses consistently clustering it with L. condylobulbon, supporting taxonomic placement despite minor ITS2-based variation. Metabolomic analysis revealed 58 distinct secondary metabolites, including 30 flavonoids, 22 terpenoids, and 6 phenolic compounds, with key bioactives such as diosmin, picrasinoside B, and 6-gingerol exhibiting known anti-inflammatory, antioxidant, and anticancer properties. Although the crude extract showed relatively low antioxidant capacity (IC₅₀ = 650 µg/mL), the chemical diversity and presence of pharmacologically active constituents underscore the species' potential for future phytotherapeutic applications.